Polyphenols and pectin enriched golden kiwifruit (Actinidia chinensis) alleviates high fructose-induced glucolipid disorders and hepatic oxidative damage in rats: in association with improvement of fatty acids metabolism - Aamina Alim; Ting Li; Tanzeela Nisar; Zeshan Ali; Daoyuan Ren; Yueyue Liu; Xingbin Yang (Food Science and Human Wellness, 2023)
This study aimed to investigate the protective effects of fleshes from two Actinidia chinensis (ACF), pericarps from two A. chinensis (ACP), and fleshes with pericarps from two A. chinensis (ACFP) on high fructose (HF)-instigated dyslipidemia, hepatic steatosis, oxidative stress, insulin resistance, and fatty acid metabolism disorders in rats. In general, the above abnormalities were improved after 10 weeks intervention of ACF, ACP, and ACFP. Especially, ACFP considerably ameliorated HF-induced abnormal changes in body weight gain, serum TC, TG, LDL-C and HDL-C levels, as well as serum and hepatic SFAs, MUFAs and PUFAs contents. ACFP also alleviated HF-induced hyperglycemia and hyperinsulinemia, stabilized HF-caused increase in hepatic MDA and serum ALT, AST levels, and restored HF-declined hepatic T-SOD and GSH-Px activities. Besides, histopathology of the liver further endorsed the protective effects of ACFP on hepatocellular injury. Moreover, ACFP increased HF-dropped acetic, propionic and butyric acid levels. Overall, ACFP employs more efficacious protective effects against HF-induced metabolic disorders and liver damage than ACF and ACP. This study delivers a scientific foundation for developing kiwifruit (counting peel)-based dietary supplements for those with glucolipid-metabolic disorders and liver damage.